Students’ Perception of Sustained Silent Reading (SSR) on Reading Comprehension in SMPN 1 Abang - Ni Made Kristin Natalia; Ni Luh Putu Eka Sulistia Dewi; Ni Putu Astiti Pratiwi (English Education Department STKIP Agama Hindu Singaraja, 2021)
Assisting students to have good reading comprehension is essential to be accomplished during learning. Sustained Silent Reading (SSR) comes as the most used strategy to promote students’ literacy and build their reading comprehension based on the pre-observation in junior high schools in Karangasem Regency. This study aimed to investigate students’ perception of using SSR to enhance students’ reading comprehension in SMPN 1 Abang. The design of the study was mixed-method. The setting of this study is SMPN 1 Abang, located in Abang district, Karangasem regency, Bali province. This study used a questionnaire as the instrument of this study. The type of questionnaire used is a mail survey, specifically the questionnaire created in scale items by using Likert-type questions. As the study results, the mean score was categorized as very high because it was 4.50 and the interval was 4.00<M<5.00. In other words, the student's perception of using SSR to enhance students’ reading comprehension in SMPN 1 Abang showed very positive qualifications. Thus, it implies that SSR is helpful to improve students’ reading comprehension.